Reinventing screen printing inspirational pieces by contemporary practitioners - Williamson, Caspar (London A&C Black, 2011)
This title is a visual treat, irresistible to designers and creatives from all backgrounds featuring informative sections on the latest techniques and applications.
Reinventing screenprinting is a visual treat, irresistible to designers and creatives from all backgrounds featuring informative sections on the latest techniques and applications.
Keywords: Screen process printing; Crafts